Analisis Perbedaan antara Perencanaan dan Kebutuhan Tenaga Kerja Aktual menggunakan Metode DMAIC untuk Produk Compact, Jar, dan Lipstick - Joshua Fernando Swanto; Prayonne Adi (Jurnal Titra, 2021)
Human resource planning in the company is needed so that the company can prepare workers before starting the production process. Planning errors can cause financial problems, production problems and other problems. This research was conducted due to the difference between planning and actual labor requirements for compact, jar and lipstick products. Planning the company's workforce needs using the help of SAP software, and the company will make adjustments on the production floor if there is an excess or lack of labor. Changes in the number of workers also make changes in labor productivity. Therefore, differences in the number of workers can be identified based on differences in the value of productivity that is planned and actual. To optimize planning, it requires root cause analysis using the DMAIC method and 5 whys analysis. By finding the root cause of the problem, the company can immediately take corrective action and improve their company.